PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI DAN PARTISIPASI MANAJEMEN TERHADAP KINERJA INDIVIDU DENGAN KEMAMPUAN TEKNIK PEMAKAI SISTEM INFORMASI AKUNTANSI SEBAGAI PEMODERASI - Ni Komang Dwi Marini; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2021)
The purpose of this research is to determine the effect of Information Technology Use and Management Participation on Individual Performance with Technical Ability of SIA Users as a moderator. A total of 14 KSUs located in Gianyar District with 60 employees were selected as locations and research samples. Probability sampling with the Slovin formula is used as the sampling method in this study. Data analysis techniques include descriptive analysis, validity test, reliability test, classical assumption test, MRA, F test, determination coefficient (R2), and t test. The results of this research show that: (1) The use of information technology has a positive effect on individual performance, with a regression coefficient of 0.285, a tcount of i2.447 and a significant value of 0.018 <0.05. (2) Management participation has a significant positive correlation on individual performance, the regression coefficient is 0.143, the tcount is 2.354 and the significant value is 0.025 <0.05. (3) The ability of the AIS user technique is able to moderate the relationship between the use of information technology and individual performance, where the regression coefficient of moderation is 0.155, the value of tcount is 2.583 and the value is significant as much as 0.013 <0.05. (4) The ability of the user technique is able to moderate the relationship between Management Participation and Individual Performance, where the regression coefficient value in moderation 2 is 0.231, the tcount value is 2.381 and the significant value is 0.021 <0.05.